Peran Bimbingan Konseling Dalam Mengatasi Anak Temper Tantrum - Fikriyah, Adela Tsamrotul; Syafi’i, Imam (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2021)
Early childhood is a time to learn to deal with feelings, whether disappointed, sad, angry when what they want is not fulfilled. That's all a natural and natural feeling. Sometimes without us realizing it we as adults clog an emotion, for example distracting a child. However, if this feeling cannot be expressed by the child, there will be a pile of emotions that can later explode and get out of control, and appear like a tamper tantrum. Expressing emotions with dangerous actions is a form of tantrums so that children get what they want or need. The older the child, the more energy he puts into expressing his emotions. Therefore it is difficult for adults to control and prevent uncontrollable behavior. The purpose of this study was to determine the role of counseling guidance in overcoming children with temper tantrums in RA Anak Salih Suwayuwo, precisely in group A children. Researchers used qualitative methods in their research. Counseling guidance at RA Anak Salih Suwayuwo is carried out through various stages of certain services.